Corticosterone rather than ethanol epigenetic programmed testicular dysplasia caused by prenatal ethanol exposure in male offspring rats. Issue 3 (4th March 2019) - Liu, Min; Zhang, Qi; Pei, Linguo; Zou, Yunfei; Chen, Guanghui; Wang, Hui
ABSTRACT: Prenatal ethanol exposure (PEE) could affect offspring's testicular development. This study aimed to illuminate its intrauterine origin and the programming mechanism caused by PEE. Pregnant Wistar rats were given ethanol (4 g/kg.d) by gavage administration during gestational days (GD) 9–20. Serum samples and testes of male offspring rats were collected on GD20, postnatal week (PW) 6, and PW12. We found that PEE induced testicular morphological abnormality, low serum testosterone levels, expressive suppression of 3β-hydroxysteroid dehydrogenase (3β-HSD), and low acetylation levels of histone 3 lysine 14 (H3K14ac) of 3β-HSD before and after birth. In utero, when fetal rats were overexposed to corticosterone by PEE, the expression levels of testicular glucocorticoid receptor (GR) and histone deacetylase 2 (HDAC2) were increased, while that of steroidogenic factor 1 (SF1) was decreased. In vitro, corticosterone (rather than ethanol) at 500 to 2, 000 nM concentration decreased testosterone production and 3β-HSD expression in a concentration-dependent manner. Moreover, corticosterone downregulated SF1 and upregulated HDAC2 via activating GR, accompanied by a low H3K14ac level of 3β-HSD; SF1 overexpression could reverse the increased HDAC2 expression, and knockdown of HDAC2 could partially reverse the inhibitory effects of corticosterone on H3K14ac level and 3β-HSD expression but not on SF1 expression. Taken together, PEE caused testicular dysplasia in male offspring rats, which was associated with corticosterone-induced low-functional programming of 3β-HSD through the GR/SF1/HDAC2/H3K14ac pathway. This study provides new academic perspectives to illuminate the theory of 'Developmental Origins of Health and Disease.'